2020
DOI: 10.1186/s40738-020-00084-1
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in fertility knowledge among women from low and high resource settings presenting for fertility care in two United States metropolitan centers

Abstract: Background: Few studies have examined health literacy and fertility knowledge among women from low income, socio-culturally diverse communities presenting for fertility care in the United States. Our study sought to examine demographic predictors of fertility-related knowledge among infertile women from low and high-resource communities in two major metropolitan centers in the United States. Methods: Fertility Knowledge Assessments were administered to women presenting for fertility care at county medical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Our finding of a positive relationship between education and reproductive biology knowledge is consistent with previous fertility knowledge studies, including 19 of 24 studies in a systematic review by Pedro et al (2018), a multi-country study (n ¼ 10,045) by Bunting et al (2013), and a study (n ¼ 143) by Hoffman et al (2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding of a positive relationship between education and reproductive biology knowledge is consistent with previous fertility knowledge studies, including 19 of 24 studies in a systematic review by Pedro et al (2018), a multi-country study (n ¼ 10,045) by Bunting et al (2013), and a study (n ¼ 143) by Hoffman et al (2020).…”
Section: Discussionsupporting
confidence: 90%
“…Pedro et al (2018) excluded income from their systematic review, whereas in their large multicountry study, Bunting et al (2013) found that respondents who had paid work or a partner with paid work had higher fertility knowledge than those who did not. In contrast, Hoffman et al (2020) found no income-related differences in fertility knowledge among infertility care clients (n ¼ 143), who are likely better informed, regardless of income, than the general population.…”
Section: Discussionmentioning
confidence: 63%
“…Although in-person interpreters are generally preferred by patients and providers, using telephonic or video interpreters during clinical encounters is effective and helps reduce patient wait times ( 64 ). Furthermore, access to straightforward information pamphlets written at grade 6–7 level and translated into common languages can help provide basic infertility information to patients in low-resource settings who often have a lower level of education and understanding of infertility ( 36 , 65 , 66 ). These educational materials can be printed materials or, through the production of short videos, posted online.…”
Section: Strategies To Improve Barriers In Access To Care Among Train...mentioning
confidence: 99%
“…[ 3 ] A recent tendency among them was observed wherein first-time parenthood was considered in late thirties. [ 4 5 6 7 ] As child conception is deferred for considerable time giving priority to professional goals, it deteriorates the probability of natural conception and subsequently requires specialized treatment to help the couples. [ 3 ] Statistics are available, emphasized the fact that there was downward trend in the total fertility rate, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] There are further evidence of lower levels of health awareness among low resource settings and individuals with lower academic qualification. [ 7 ] Looking into all the aspects, it is apparent that infertility is progressively becoming alarming and a public health issue.…”
Section: Introductionmentioning
confidence: 99%